Competitive strategies and entry strategies of low cost airline incumbent 1time Airline - Potgieter, Diane (Rhodes University, Faculty of Commerce, Investec Business School, 2007)
This dissertation reports on the factors that contributed to the successful entry strategy of 1time Airline, a low cost carrier, into the South African airline industry as well as its competitive strategies within this context. Research interviews were conducted in November 2005 and research material gathered until end January 2006. Key issues include an evaluation of 1time's business model in relation to other low cost entrants as well as against material sourced through interviews with 1time Airline management, employees and consumers of the airline's product. Porter's Generic Strategies and Five Forces model are used as a framework in evaluating the airline. It is found that Nohria, Joyce and Robertson's "4+2 Formula" is effectively implemented at the airline, but that further implementation of Game Theory in terms of alliances should be investigated for continued success and sustainability.
Keywords: 1time Airline (South Africa); 1time Airline (South Africa) -- Planning; Airlines -- South Africa -- Management; Airlines -- South Africa -- Marketing; Airlines -- South Africa -- Cost of operation; Competition -- South Africa; Strategic planning